New technical solutions for construction of the Minsk ring highway - Leonovich, Ivan Iosifovich; Bogdanovich, Sergey Valerevich (Technological and Economic Development of Economy, 2004)
In Byelorussia the network of highways intensively develops. For their construction and reconstruction modern technologies are used. The sample of new technical decisions in road construction can be counted the Minsk ring highway. Questions of erection of an earthen cloth on bogs have been here successfully solved. Geosynthetic materials, blacktop with cellulose fibres, noise protection screens from profile metal are used. Construction of bridges and overpasses was carried out with wide application of preliminary intense bearing designs. The bridge cloth and sidewalks are executed from monolithic concrete. For strengthening slopes, ridge vibropressing plates are applied. All works were carried out by wide front with maximal use of high‐efficiency road technics. With the purpose of management of a condition roadway parts on the Minsk belt line three road measuring stations are constructed. They allow to carry out works under the account of transport streams and influences of meteorological‐climatic factors on the traffic‐operational condition of a highway.Article in Russian.Новые технические решения при строительстве Минской кольцевой автомобильной дорогиNauji techniniai sprendimai tiesiant Minsko žiedinį keliąFirst Published Online: 21 Oct 2010